Chemical Polymerization Kinetics of Poly-O-Phenylenediamine and Characterization of the Obtained Polymer in Aqueous Hydrochloric Acid Solution Using K2Cr2O7 as Oxidizing Agent. (12th June 2014) - Sayyah, S. M.; Khaliel, A. B.; Aboud, Ahmed A.; Mohamed, S. M.
Abstract : The oxidative chemical polymerization of o-phenylenediamine (OPDA) was studied in hydrochloric acid solution using potassium dichromate as oxidant at 5°C. The effects of potassium dichromate, hydrochloric acid, and monomer concentrations on the polymerization reaction were investigated. The order of reaction with respect to potassium dichromate, hydrochloric acid, and monomer concentration was found to be 1.011, 0.954, and 1.045, respectively. Also, the effect of temperature on the polymerization rate was studied and the apparent activation energy of the polymerization reaction was found to be 63.658 kJ/mol. The obtained polymer was characterized using XPS, IR, UV-visible, and elemental analysis. The surface morphology of the obtained polymers was characterized by X-ray diffraction and transmission electron microscopy (TEM). The TGA analysis was used to confirm the proposed structure and number of water molecules in each polymeric chain unit. The ac conductivity ( σ ac ) of (POPDA) was investigated as a function of frequency and temperature. The ac conductivity was interpreted as a power law of frequency. The frequency exponent (s) was found to be less than unity and decreased with the increase of temperature, which confirms that the correlated barrier hopping model was the dominant charge transport mechanism.